Pleistocene Geology of the Embarrass Area, St. Louis County, Minnesota - Lehr, James Davis (2000)
A Thesis submitted to the faculty of the Graduate School of the University of Minnesota by James Davis Lehr in partial fulfillment of the requirements for the degree of Master of Science, May 2000. This item has been modified from the original to redact the signatures present. Plates I-III referenced in the thesis are also attached to this record. (Plate II has a map on one side and an explanation on the other.) Minnesota's landscapes and surficial deposits have resulted from the interaction of late Cenozoic continental glaciers upon a weathered bedrock surface. Erosion and deposition during subsequent glacial stages have largely obscured the effects of earlier glaciations. During the late Wisconsinan Stage, the Laurentide Ice Sheet advanced into Minnesota several times, becoming lobate as the ice followed preexisting regional bedrock lowlands. Each lobe of ice deposited a lithologically distinct drift, reflecting the nature of the bedrock over which it flowed. This thesis is one in a continuing sequence of detailed studies of geomorphology, sedimentology, stratigraphy, and drift lithology intended to clarify the complex glacial history of Minnesota. The Embarrass area was selected for study because of its importance to understanding the style and chronology of deglaciation in northern Minnesota.